American economic journal : applied economics - American Economic Association (Pittsburgh, PA American Economic Association, 2011)
The Journal publishes papers covering a range of topics in applied economics, with a focus on empirical microeconomics issues. In particular, we welcome papers on labor economics, development microeconomics, health, education, demography, empirical corporate finance, empirical studies of trade, and empirical behavioral economics.
American economic journal : applied economics is published Quarterly Jan, April, July, October
Keywords: Economics; ECONOMICS; ECONOMIC POLICY; PERIODICALS